Preparation of La₂O₃-CaO mixed oxide catalysts supported on nanostructured activated carbon for biodiesel production from waste cooking oil - Abdulkreem, Abdulkareem Ghassan (2016)
Advanced carbon nanorod promoted binary La2O3-CaO system with improved physical properties, tailored surface morphology and chemistry were developed in vacuum-impregnating methods. The nanostructured catalyst (CaO–La2O3/AC nanocatalyst) was prepared to convert waste cooking oil with high FFA into biodiesel via one step esterification-transesterification reaction. The novel catalyst was characterized by XRF, FTIR, HRTEM, FESEM, XRD, TGA, BET, TPD-CO2 and TPD-NH3. The high catalytic activity of the nanocatalyst was mainly depended on the high acid and basic density of active sites that contributed from the synergic effect between mesoporous carbon and binary metallic system, which allowed more occurrence of simultaneous esterification-transesterification process of high FFA waste oil without additional pretreatment step. Results showed a maximum triglyceride conversion of 98.6 ± 0.5% with acid value 0.4 ± 0.5 mg KOH/g of triglyceride conversion under optimal condition at 3% of catalyst, methanol: oil ratio of 16:1, 100 oC within 4 h of reaction. Furthermore, bi-metallic catalysts with stable carbon nanorod support were capable to maintained high reusability with high FAME yield (> 98%) with low acid value (<0.5 mg KOH/g) for 5 cycles. Several physicochemical properties of WCO-based biodiesel produced were tested and in good agreement to ASTM D6751 standards.